2009
DOI: 10.1017/s0022112009992801
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation and large-eddy simulation of stationary buoyancy-driven turbulence

Abstract: We report direct numerical simulation (DNS) and large-eddy simulation (LES) of statistically stationary buoyancy-driven turbulent mixing of an active scalar. We use an adaptation of the fringe-region technique, which continually supplies the flow with unmixed fluids at two opposite faces of a triply periodic domain in the presence of gravity, effectively maintaining an unstably stratified, but statistically stationary flow. We also develop a new method to solve the governing equations, based on the Helmholtz-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Similar results were achieved with the WENO-TCD scheme (Hill & Pullin 2004). Using the same SGS model and the Fourier pseudospectral method, Chung & Pullin (2010) performed DNS and LES of statistically stationary buoyancy-driven turbulent mixing, showing that both the resolved-scale and SGS-extended components of the LES velocity spectra and velocity-density cospectra accurately capture important features of the DNS. Comparisons between LES and DNS initiated by the Taylor-Green vortex (Drikakis et al 2007) demonstrated that a variety of explicit SGS models and implicit LES models (Grinstein, Margolin & Rider 2007) can consistently capture the physics of turbulence decay.…”
Section: Methodssupporting
confidence: 53%
“…Similar results were achieved with the WENO-TCD scheme (Hill & Pullin 2004). Using the same SGS model and the Fourier pseudospectral method, Chung & Pullin (2010) performed DNS and LES of statistically stationary buoyancy-driven turbulent mixing, showing that both the resolved-scale and SGS-extended components of the LES velocity spectra and velocity-density cospectra accurately capture important features of the DNS. Comparisons between LES and DNS initiated by the Taylor-Green vortex (Drikakis et al 2007) demonstrated that a variety of explicit SGS models and implicit LES models (Grinstein, Margolin & Rider 2007) can consistently capture the physics of turbulence decay.…”
Section: Methodssupporting
confidence: 53%
“…Although RT turbulence is of great importance and has been studied for many decades, there are still some open issues 10,11 . Specifically, for the past decade, many studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] have focused on small-scale turbulent fluctuations in both two-(2D) and three-dimensional (3D) RT turbulence. In two dimensions, Chertkov 15 proposed a phenomenological theory.…”
Section: Introductionmentioning
confidence: 99%
“…All DNS solutions satisfied standard convergence criteria [15] (with grid spacing l , the Kolmogorov scale). The subgridscale model in the LES was based on a dynamic eddy viscosity and eddy diffusivity (with l 10), as previously shown to be accurate for convection [16][17][18][19] (the detailed algorithms are found in [20,21]). The LES solutions were also validated against the DNS solutions at Ra 6 Â 10 8 and showed no significant differences (in heat transport, volume integrals and vertical profiles of energy conversion terms, and dissipation spectra).…”
mentioning
confidence: 99%